Immunoregulation of Quercetin and Kynurenic Acid on Human Umbilical Cord Mesenchymal Stem Cells Through Gene Expression of Aryl Hydrocarbon Receptor and Interleukin-6 in Hyperglycemic Milieu - Thi Sam Nguyen; Thi Thuy Ngan Nguyen; Thi Phuong Anh Nguyen; Tran Bao Chau Ha; Manh Cuong Nguyen; Syed Shadab Raza; Vinh Truong Do; Hoang Ha Chu (Stem Cells International)
Mesenchymal stem cells (MSCs) exhibit great promise for treatment applications because of their immunosuppressive properties. The aryl hydrocarbon receptor (AHR), which is a transcription factor that is activated via ligand, has a pivotal role in regulating the immune system and is involved in a range of immune-related disorders. However, hyperglycemia, the defining biochemical hallmark of diabetes, creates a chronically pro-inflammatory microenvironment that impairs the immunoregulatory effects of MSCs. In this study, we explored the potential of kynurenic acid (KYNA) and quercetin, two naturally derived compounds, to modulate the immune response of MSCs through the regulation of AHR signaling under hyperglycemic conditions. We assessed the immunophenotyping and differentiation capacity of cultured human umbilical cord mesenchymal stem cells (hUC-MSCs) in a high-glucose medium and quantified the mRNA expression rate of AHR, CYP1A1, CYP1B1, and IL-6 using real time PCR. Our study is the first to reveal that KYNA and quercetin enhance mRNA expression levels of AHR and CYP1B1, while reducing IL-6 expression in hUC-MSCs, suggesting their potential as immunomodulators. These findings highlight the compounds’ promise as drug candidates for immune-mediated diseases through stem cell therapy, particularly due to their modulation of AHR.